2019
DOI: 10.1080/0142159x.2018.1552784
|View full text |Cite
|
Sign up to set email alerts
|

AMEE Guide No. 123 – How to read studies of educational costs

Abstract: Healthcare and health professions education share many of the same problems in decision making. In both cases, there is a finite amount of resources, and so choices need to be made between alternatives. To navigate the options available requires effective decision making. Choosing one option requires consideration of its opportunity cost -the benefit forgone of the other competing options.The purpose of this guide is to introduce educational decision-makers to the economic concept of cost, and how to read stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…This will allow us to evaluate if the adapted MMI has comparable predictive validity to our "usual" (non-COVID-19) MMI, and MMIs reported in the literature. Additionally, there has been increasing focus on the cost-effectiveness of medical education generally (Maloney et al 2019), selection into medical school specifically (Schreurs et al 2018). Taking the view that every cloud has a silver lining, we have the opportunity for a natural cost-benefit analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This will allow us to evaluate if the adapted MMI has comparable predictive validity to our "usual" (non-COVID-19) MMI, and MMIs reported in the literature. Additionally, there has been increasing focus on the cost-effectiveness of medical education generally (Maloney et al 2019), selection into medical school specifically (Schreurs et al 2018). Taking the view that every cloud has a silver lining, we have the opportunity for a natural cost-benefit analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of costs can be used to improve education programmes, firstly from a summative view in terms of the identification of which is a more cost‐effective option between programmes, but also from a formative view in the identification of cost drivers within a programme . Although value matters more than cost alone, judgements of value are highly context‐dependent and will depend on the perspective of the decision maker and the objectives of the educational intervention . Therefore, accurate and full evaluations of costs, reported in a complete manner, are necessary for cost evaluations to inform decision making.…”
Section: Introductionmentioning
confidence: 99%
“…While two articles included information related to the expense of course development (50,000 Euros and 10,000-50, 000 dollars) [28,46], no studies reported outcome measures relating to either a simple cost or value analysis, or comparative costs in the form of cost-benefit or cost-effectiveness analysis. We looked for evidence across the full spectrum of cost and value analyses, including cost-analyses (where outcomes are not considered), and breakeven analyses, and comparative approaches such as cost-minimisation analyses (where the outcomes are assumed equal), cost-benefit analyses (where costs and effects are considered in monetary units), and cost-effectiveness analyses (where outcomes are retained in natural units, such as measures of learning) [67,68].…”
Section: Economicsmentioning
confidence: 99%